Sloan Peacock :capstone - Peacock, Sloan, artist (Colorado State University. Libraries, 2023)
The artist's statement: My work seeks to effectively marry communication and aesthetics. With a multitudes of influences and experiences, I have worked to build an arsenal of design skills to utilize for any situation. I strive to create work that fits perfectly into any client's brand. I have been interested in artwork for my whole life. Keeping a sketchbook with me wherever I go for most of my life. I am fascinated by all types of artworks; the design world is ever-changing and I believe that it is important for artists to be flexible and prepared to learn and grow with it. I will graduate with a Bachelor of the Fine Arts with a concentration in Graphic Design from Colorado State University in May of 2023. In addition to design classes, I have taken multiple classes in Printmaking and Photo Image Making to round out my skill set.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design